Stevens-Johnson syndrome and toxic epidermal necrolysis: a review - Ruiz, Rodrigo Banegas; Valderrama Treviño, Alan I.; F., Gómez Mendoza F.; R., Baca Domínguez C.; G., Campos Angulo; F., Alejo Fuentes L.; N., Jiménez Nateras C.; Manuel, Ramos-Lojero Víctor; A., Espejel Blancas J.; Mera, Baltazar Barrera (International Journal of Research in Medical Sciences, 2019)
Stevens Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) are considered a single entity with variability in the extent of the lesions, characterized by erythema multiforme that may involve mucosa. Severe cutaneous reactions secondary to medications are classified according to the area of epidermal detachment. The activation of cytotoxic T cells and macrophages is mediated mainly by IL-2 and interferon gamma secreted by Th1 lymphocytes, and the activation of eosinophils and B lymphocytes in IgE is mediated by secreted IL-4, IL-5, IL-10 and IL13 by B lymphocytes. The topography of SJS is predominantly central, affecting the trunk and sometimes a generalized dissemination is shown that affects a body surface area of less than 10%, characterized by irregular violaceous erythematous macules of target shooting, which can form confluent blisters. TEN is characterized by a skin detachment greater than 30% of the body surface, whose predominant lesion is diffuse erythema with individual macules, which give rise to detachment surfaces greater than 5 cm. The treatment is symptomatic, nonspecific, and aimed at avoiding complications, carried out in specialized intensive care units, due to ignorance of the pathogenesis. Integral management with different therapeutic alternatives can represent a crucial part in the multisystemic management of SJS and TEN.